Prestress losses in pretensioned concrete beams cast with lightweight self-consolidating concrete. (June 2015) - Bymaster, Jared C.; Dang, Canh N.; Floyd, Royce W.; Hale, W. Micah
Abstract: The use of lightweight self-consolidating concrete (LW-SCC) for pretensioned concrete members offers advantages over the use of conventional, normal weight concrete. This study focused on investigating the prestress losses of 12 pretensioned concrete beams cast with LW-SCC or normal weight SCC (NW-SCC). Two LW-SCC mixtures were developed along with one NW-SCC mixture. The LW-SCC mixtures contained expanded shale or expanded clay coarse aggregates. Prestress losses were measured using vibrating wire strain gauges. The beams were loaded approximately 150 days after casting and losses were measured for an additional 75 days after casting. In addition to prestress losses, the modulus of elasticity (MOE) and shrinkage of the mixtures were measured. Experimental results indicated that the AASHTO-LRFD equation for MOE using a correction factor of 1.0 is appropriate to predict the MOE of LW-SCC. Shrinkage of LW-SCC was less when compared to NW-SCC due to the effect of internal curing. CEB MC90 was the most appropriate model to predict concrete shrinkage. The AASHTO-LRFD methods over-estimated instantaneous and long-time prestress losses. The AASHTO approximate method was more suitable to estimate total prestress losses for the beams using LW-SCC than the AASHTO refined method.